Community-Onset Bloodstream and Other Infections, Caused by Carbapenemase-Producing Enterobacteriaceae: Epidemiological, Microbiological, and Clinical Features. (1st August 2016) - Paño-Pardo, José Ramón; López Quintana, Beatriz; Lázaro Perona, Fernando; Ruiz Carrascoso, Guillermo; Romero-Gómez, María Pilar; Loeches Yagüe, Belén; Díaz-Pollán, Beatriz; Martínez-Virto, Ana; Mingorance, Jesús; García Rodríguez, Julio; Arribas, José Ramón; Gómez-Gil, Rosa
Abstract: Background. Because most infections caused by carbapenemase-producing Enterobacteriaceae (CPE) begin during hospitalization, there are limited data about community-onset (CO) infections caused by CPE. Our aim is to describe the frequency of CO infections caused by CPE as well as the clinical features of CO bloodstream infections (CO-BSIs). Methods. This study includes retrospective case series of CO infections caused by CPE in a tertiary hospital from January 2010 to July 2014. Any clinical sample with a positive culture for CPE that had been ordered by primary care doctors or by doctors at the emergency room (ER) were classified as CO. Epidemiological and microbiological features of CO cases were assessed as were clinical features of CO-BSIs. Results. Of 780 clinical samples with CPE, 180 were requested at the ER or by primary care doctors (22.9%), 150 of which were produced by Klebsiella pneumoniae (83.3%). The blaOXA−48 gene was detected in 149 isolates (82.8%) followed by the blaVIM gene, 29 (16.1%). Sixty-one patients (33.9%) had a prior history of CPE infection/colonization. Thirty-four of the 119 (28.6%) patients without prior history of CPE infection/colonization did not fulfill Friedman criteria for healthcare-associated infections (HAIs). Considering previous hospitalization of up to 12 months as a criterion for defining HAI, only 16 (13.4%) cases were identified as community-acquired infections. The most frequent positive sample was urine (133 of 180; 73.9%). Twenty-one (11.7%) patients had a BSI, 9 of them secondary to urinary tract infections (42.9%). Thirty-day crude mortality among patients with BSI was 23.8% (5 of 21). Conclusions. Community-onset infections caused by CPE are an important subgroup of all CPE infections. The urinary tract is the main source. Bloodstream infections accounted for more than 10% of the cases.